Optimizing Interactive Infographics: A Needs Study for The Development of Begrüßung Materials in German Language Teaching at SMAN 14 Palembang - Krisnatalety, Krisnatalety; Raharjo, Makmum; Susanti, LR. Retno (Journal of Educational Sciences, 2025)
This study aims to develop interactive infographic-based learning media to enhance the effectiveness of German language teaching, particularly for the Begrüßung material at SMAN 14 Palembang. The research utilized a descriptive qualitative method to analyze the needs of both students and teachers through questionnaires, classroom observations, and interviews. The results show that the majority of students (63%) and teachers (79%) perceive a high need for the development of interactive learning media, particularly infographics that support engagement and material comprehension. Data from the learner needs analysis revealed that 63% of students are in the "high" category, with a significant need for innovation in media, while 29% fall into the "medium" category. Similarly, 79% of teachers expressed the need for such media to improve teaching effectiveness. Interactive infographics, especially those incorporating quizzes and audio, are expected to increase student engagement and improve learning outcomes. The study concludes that interactive infographic-based media can address the challenges in language learning, offering a more inclusive and engaging experience. Furthermore, the research provides a solid foundation for designing adaptive learning media aligned with the needs of both students and teachers in the digital era.